2017
DOI: 10.1158/0008-5472.can-16-2529
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-194 Promotes Prostate Cancer Metastasis by Inhibiting SOCS2

Abstract: Serum levels of miR-194 have been reported to predict prostate cancer recurrence after surgery, but its functional contributions to this disease have not been studied. Herein, it is demonstrated that miR-194 is a driver of prostate cancer metastasis. Prostate tissue levels of miR-194 were associated with disease aggressiveness and poor outcome. Ectopic delivery of miR-194 stimulated migration, invasion, and epithelial-mesenchymal transition in human prostate cancer cell lines, and stable overexpression of miR-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 59 publications
4
85
1
Order By: Relevance
“…Whilst this manuscript was in revision, Das and colleagues reported the selective advantage in promoting PCa metastasis upon inhibition of SOCS2 (Das et al, 2017), which is one of the genes we found to be attenuated by MYC overexpression. Furthermore, a re-analysis of a comprehensive study by Taylor and colleagues (Taylor et al, 2010) profiling transcriptomics of PCa showed that the expression of SOCS2 is lowest in metastases found in patients treated with castration (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Whilst this manuscript was in revision, Das and colleagues reported the selective advantage in promoting PCa metastasis upon inhibition of SOCS2 (Das et al, 2017), which is one of the genes we found to be attenuated by MYC overexpression. Furthermore, a re-analysis of a comprehensive study by Taylor and colleagues (Taylor et al, 2010) profiling transcriptomics of PCa showed that the expression of SOCS2 is lowest in metastases found in patients treated with castration (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have indicated that the expression of MMP-2 and MMP-9 is associated with EMT, and vimentin is often used as a marker of mesenchymally derived cells or cells undergoing EMT during both normal development and metastatic progression [51,52]. However, the STAT3 signaling pathway has been shown to be involved in tumor EMT [53]. Our results showed that allicin significantly inhibits the migration and invasion capacity of CCA cells and reduces the expression of MMP-2/9 and vimentin, but increases E-cadherin protein levels in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Stable LNCaP-shGRHL2 cell lines were generated using GRHL2-specific shRNA plasmids (TRCN0000015808 and TRCN0000015810) and an shRNA control plasmid (Shc002) from Sigma as described previously (7). …”
Section: Methodsmentioning
confidence: 99%
“…CAM assays were approved by the University of Adelaide Animal Ethics Committee (approval number M-2014_079) and done using the in ovo method as described previously (7). …”
Section: Methodsmentioning
confidence: 99%